A Synaptic Electrochemical Memristor Based on the Cu2+/Zn2+Cation Exchange in Zn:CdS Thin Films - Congiu, Mirko [UNESP]; Boratto, Miguel H.; Graeff, Carlos F. O. [UNESP] (Wiley, 2018)
Neuromorphic hardware systems that simulate functions of biological brain synapses have been widely investigated due to their possible application in brain-inspired computing. We hereby report on a novel electrochemical state machine based on Zn:CdS thin films. The memory switching mechanism involves the cation exchange of Cu2+ and Zn2+ acting as inorganic “neurotransmitters”. Similarly to the synapse-neurotransmitter interactions, Cu2+ ions increase the conductivity and the electrocatalytic activity of Zn:CdS towards the ferrocene/ferrocenium redox process. The cationic substitution of Zn2+ by Cu2+ in the film has shown significant changes in the electrochemical characteristic of the device. Such effects have been investigated with both alternated current (impedance) and direct current (voltammetry and I vs V) measurements. The cation exchange mechanism allows to write and store an electrochemical information into the device. Such information can be gradually erased by exchanging the absorbed Cu2+ ions with Zn2+. By means of a timed soaking, of the active area, with Cu2+ and Zn2+ diethyldithiocarbamates, the device can be driven through multiple conduction states, making it suitable for applications in artificial synapses research and memory storage systems.
Keywords: Electrochemical; memory; memristors; neuromorphic; synaptic